Czy istnieje optymalna metoda prowadzenia seminarium magisterskiego? - Drabik, Ewa (Does It Exist an Optimal Method of Leading a Seminar for Candidates for Master's Degree?, 2006)
In 2004 & 2005 I led a seminar for candidates for master's degree at Warsaw Agricultural University. The students of computer science and econometrics, who took part in my seminar add just started the course of financial theory, and they did not formulate their thesis. Therefore I wondered how I should work out a plan of this seminar. I wanted the classes to be constructive. My aim was not only to broaden the knowledge of my students but also to prepare them thoroughly for writting M. A. thesis. As far as I know young people (university students) have huge difficulties in writing scientific papers. I decided to explain to them the technics of composing such papers. There were 7 lectures devoted the best methods of writting. Next I asked them to write a short article concerning the capital market. I encouraged the development of their own ideas and allowed them a free hand in choosing a subject.Moreover I emphasized that I expected original, creative works containing interesting facts connected with financial markets as well as investors. The articles should have been finished before the end of semestr. Then I corrected and improved the articles. I asked the students to get ready for the presentation of their papers.The aim of this article is to share my observation with you and to find the answer to the question why such a form of classes didn't bring to expected results.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1117, s. 33-39